It is all in the details: A bilateral approach for modelling trade agreements at the tariff line - Yaghoob Jafari; Mihaly Himics; Wolfgang Britz; Jayson Beckman (Canadian Journal of Agricultural Economics/Revue canadienne d'agroeconomie, 2021)
Policymakers are increasingly relying on computable general equilibrium (CGE) models to provide economy-wide impacts of trade agreements; however, these assessments often make the simplifying assumption of complete bilateral tariff elimination. But agreements typically involve partial tariff elimination for sensitive sectors—which are often differentiated at the tariff line. As such, applying a uniform tariff reduction in a CGE sector that encompasses many products could introduce bias. We propose a tariff line approach for modelling exemptions for sensitive goods in CGE models with the aim of reducing this bias. This approach is tested for the Canada–EU trade agreement, and systematically compared to standard approaches to bilateral trade liberalisation in CGE analysis. We find that more common approaches might systematically overestimate trade and welfare impacts by neglecting partial liberalisation in selected sectors and/or not considering substitution across tariff lines.
Keywords: 330; aggregation bias; CETA; computable general equilibrium; free trade agreements; sensitive products; tariff line analysis; trade policy